2015
DOI: 10.1088/0963-0252/24/6/065019
|View full text |Cite
|
Sign up to set email alerts
|

Quantum states of confined hydrogen plasma species: Monte Carlo calculations

Abstract: The diffusion Monte Carlo method with symmetry-based state selection is used to calculate the quantum energy states of H 2 + confined into potential barriers of atomic dimensions (a model for these ions in solids). Special solutions are employed, permitting one to obtain satisfactory results with rather simple native code. As a test case, u 2 Π and g 2 Π states of H 2 + ions under spherical confinement are considered. The results are interpreted using the correlation of H 2 + states to atomic orbitals of H ato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 41 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…Reference [50] investigates the molecular ion inside padded prolate spheroidal cavities with arbitrary nuclear positions. References [51,52] by the same authors investigate the spherically confined molecular ion in the 2 Σ + g and 2 Σ + u states, and in the 2 Π g and the 2 Π u states, respectively, using the Monte Carlo approach.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [50] investigates the molecular ion inside padded prolate spheroidal cavities with arbitrary nuclear positions. References [51,52] by the same authors investigate the spherically confined molecular ion in the 2 Σ + g and 2 Σ + u states, and in the 2 Π g and the 2 Π u states, respectively, using the Monte Carlo approach.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…"Quantum states of confined hydrogen plasma species: Monte Carlo calculations" [52] implements the diffusion Monte Carlo method with symmetry-based state selection to calculate the excited states 2 Π u and 2 Π g of H + 2 ions under spherical confinement. Special solutions are employed, permitting to obtain satisfactory results with rather simple native code.…”
Section: Diatomic Hydrogen-like Ion and Neutral Molecules And Two-elmentioning
confidence: 99%
“…We found that the lowest excited states of the + H 2 molecule (the ∑ u , ∏ g and ∏ u ones) in spherical confinement conditions have potential energy surfaces (PESs) similar to those of the ground state, even if, without confinement, they are repulsive states (figures 1(a), (b)) (Micca Longo et al 2015aLongo et al , 2015b. The energy reference of any curve in figure 2(b) is the same and has been chosen in such a way that, asymptotically at = +¥ d , the energy of the unconfined system H(1s)+H + is equal to zero.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, in recent years we have developed a suite of DMC codes designed for the study of hydrogen-based and nano species confined by infinite potential wells of various geometries (Micca Longo et al 2015a, 2015b, 2015c, Longo et al 2018. In contrast with previous Monte Carlo calculations (Sarsa and Le Sech 2012), our programs do not employ analytic guess wavefunctions to reduce variance by the importance sampling technique.…”
Section: Introductionmentioning
confidence: 99%
“…Two cases of study are presented: the first one with the hydrogen nucleus fixed at the center of the confining sphere, the second one with the nucleus placed in different positions along the x axis, and in particular the equilibrium one. Using a direct calculation method based on diffusion Monte Carlo (DMC) [46][47][48], we will consider strong electric fields and different positions of the nucleus, especially the one that corresponds to the minimum overall energy, taking into account both the ground and excited states, 1s and 2p.…”
mentioning
confidence: 99%